Bromination improves the electron mobility of Tetraazapentacene - Reiß, Hilmar; Han, Jie; Koser, Silke; Tverskoy, Olena; Freudenberg, Jan; Hinkel, Felix Peter; Dreuw, Andreas; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2018)
A fully air‐stable radical anion is formed from a bis‐TIPS‐ethynyl‐substituted tetraazapentacene with four bromine substituents attached in the 2‐, 3‐, 9‐, and 10‐positions. The deep‐lying LUMO (i.e....